ANALISIS KOLABORASI ORANG TUA DAN SEKOLAH DALAM MEWUJUDKAN DIMENSI KOLABORASI PADA 8 PROFIL LULUSAN SISWA KELAS V DI SDN BULUBONGGU - Supaira; Saidang; Haerusman; Muh. Idham Haliq; Wulandari (STKIP Subang, 2026)
This study aims to describe the forms of collaboration between parents and schools in realizing the collaboration dimension of the 8 Graduate Profiles, identify supporting and inhibiting factors, and analyze school efforts to improve partnerships with parents. The study was conducted at Bulubonggu Elementary School, Dapurang District, Pasangkayu Regency, using a descriptive qualitative approach with data collection techniques including interviews, observation, and documentation. The results indicate that collaboration between parents and schools remains formal and incidental, dominated by one-way communication through parent-teacher meetings and WhatsApp groups. Supporting factors for collaboration include the use of digital communication media and open school policies, while the main inhibiting factors are parents' busy work schedules and a lack of understanding of the 8 Graduate Profiles concept. Based on behaviorist theory, the development of collaborative character in students is not optimal because the stimulus provided by the school is not followed by consistent reinforcement within the family environment. This study recommends strengthening two-way communication and a more structured and sustainable collaboration program.